Mapping Narrations - Narrating Maps : Concepts of the World in the Middle Ages and the Early Modern Period - Baumgärtner, Ingrid; Gneckow, Daniel; Hollenbach, Anna; Landgrebe, Phillip (2022)
This volume offers the author's central articles on the medieval and early modern history of cartography for the first time in English translation. A first group of essays gives an overview of medieval cartography, illustrating the methods of cartographers. Another analyzes world maps and travel accounts in relation to mapped spaces. A third examines land surveying, cartographical practices of exploration, and the production of Portolan atlases.